Application of fluorescent turn-on aptamers in RNA studies. (17th June 2021) - Al Mazid, Mohammad Faysal; Shkel, Olha; Kharkivska, Yevheniia; Lee, Jun-Seok
Abstract : Fluorescent turn-on aptamer strategies shed light on cellular RNA for imaging and further facilitate the determination of the dynamic regulation of transcriptomic research. Abstract : RNA is an intermediate player between DNA transcription and protein translation. RNAs also interact with other macromolecules and metabolites and regulate their fate. The emerging number of RNA identifications expanded new areas of study to determine their applicability and functional analysis. Recently, extensive research has been focused on visualizing RNA in living biological samples and a method has been developed by the evolution of specific fluorophore-binding aptamers through the Systematic Evolution of Ligands by Exponential Enrichment (SELEX) method. Several promising fluorescent turn-on aptamers are currently available, and they can detect RNA–RNA, RNA–protein, ligand binding, small molecule, and metabolite interactions in vitro and under live-cell conditions. Here we review the currently available fluorescent turn-on aptamers and discuss their applicability for analyzing the fate of targeted RNAs in in vitro and in vivo systems.